Good's syndrome and recurrent leishmaniasis: A case report and review of literature. Issue 9 (September 2020) - Tolomeo, Manlio; Bonura, Silvia; Abbott, Michelle; Anastasia, Antonio; Colomba, Claudia; Cascio, Antonio
Abstract: We report the case of a 56-year-old Caucasian male affected by thymoma and myasthenia gravis that developed recurrent visceral leishmaniasis 11 years after thymectomy. After treatment of each relapse with liposomal amphotericin B the PCR- Leishmania was negative and the patient showed clinical improvement. An immunologic work-up was performed showing lymphopenia with an important decrease in CD4+ T cells (52 cells/μ) and CD4/CD8 ratio (0.2). HIV test was negative. On the basis of previous thymoma and myasthenia gravis and on the basis of the immunological profile a diagnosis of Good's syndrome was made. Since IFNγ plays a main role in the control of Leishmania infection the production of IFNγ was evaluated. After mitogen stimulation of peripheral blood mononuclear cells the production of IFNγ was lower than normal. This is the second reported case of Good's syndrome with recurrent leishmaniasis and indicates that a definitive cure for leishmaniasis in patients with Good's syndrome is not possible. Immunologic work-up in our patient strongly suggests that relapses could be correlated with the low CD4+ T cell number and with the low IFNγ production. Immunotherapy with IFNγ or with compounds able to block the Th2 interleukin production could be a therapeutic option in these patients. Abstract : Infectious Disease; Immunology; Intensive Care Medicine; Internal Medicine; Laboratory Medicine; Good's syndrome; Leishmaniasis; liposomal amphotericin B; CD4+ T cells; IFNγ.